2021
DOI: 10.1101/2021.10.14.464411
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Wild cereal grain consumption among Early Holocene foragers of the Balkans predates the arrival of agriculture

Abstract: Forager focus on wild cereal plants has been documented in the core zone of domestication in southwestern Asia, while evidence for forager use of wild grass grains remains sporadic elsewhere. In this paper, we present starch grain and phytolith analyses of dental calculus from 61 Mesolithic and Early Neolithic individuals from five sites in the Danube Gorges of the central Balkans. This zone was inhabited by likely complex Holocene foragers for several millennia before the appearance of the first farmers ~6200… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…This is because the botanical material in archaeological contexts is almost always lost and, that which survives, would need of specific molecular/ genetic identification. However, recent methods applied to dental calculus have provided a wide understanding of the dietary preferences of human and animal and their interaction with the environment [1][2][3][4] .…”
mentioning
confidence: 99%
“…This is because the botanical material in archaeological contexts is almost always lost and, that which survives, would need of specific molecular/ genetic identification. However, recent methods applied to dental calculus have provided a wide understanding of the dietary preferences of human and animal and their interaction with the environment [1][2][3][4] .…”
mentioning
confidence: 99%
“…7), were also identified in reasonable quantities as millet starch grains. Previous experimental analyses in species of the Triticeae tribe have revealed that wild starch grains (Aegilops genus) show a larger size distribution than domestic ones (Triticum and Hordeum genus) 78,79 . Additionally, B-type grains are more abundant than A-type in wheat and barley species.…”
Section: Dental Calculus Evidence Of Millet Consumptionmentioning
confidence: 99%